Immobilization of adult male southern elephant seals (Mirounga leonina) during the breeding and moulting periods, using Zoletil® (tiletamine/zolazepam) and ketamine - Carlini, A. R.; Negrete, Javier; Daneri, Gustavo Adolfo; Rogers, Tamara Belén; Márquez, María Elba Isabel; Ciaglia, M.; Mennucci, Jorge Augusto (Polar Biology)
Seventy-seven immobilizations were carried out on adult male southern elephant seals at Stranger Point, Isla 25 de Mayo (King George Island) using a combination of Zoletil (tiletamine and zolazepam) and ketamine in order to obtain biological samples. During 2006/2007, 22 males were immobilized at the beginning of their breeding period (EB), 19 of which were recaptured at the end of breeding (LB). Four were given only once at an unknown stage of breeding (USB) and 18 males were immobilized at the beginning of molting (BM). During 2007/2008, 14 adult males were immobilized at an USB. Zoletil was administered using an automatic discharge device, whereas ketamine was injected directly with a syringe, and was used only when the initial sedation was not enough to carry out the programmed sampling. The initial mean dose of Zoletil was 1,387 ± 304 mg, which represented 0.60 ± 0.14 mg/kg, range 0.36–1.05, n = 77. In 47 procedures, an average dose of 1.04 ± 0.66 mg/kg of ketamine was added. Mean immobilization time was 34 ± 14 min. In 25 out of the 77 procedures, males showed apnea, which lasted 8 ± 4 min (range 2–15 min). The necessary doses of Zoletil and ketamine to attain immobilization differed between stages. For animals taken twice, doses (mg/kg) of Zoletil and ketamine were significantly higher at the beginning than at the end of breeding. During molting, the doses of Zoletil given were significantly lower than those used during breeding, although the proportion of animals that required ketamine during molting was significantly higher than during breeding. Zoletil proved to be a safe immobilizing agent for field work on adult males of this species, given the wide range of doses used without any serious consequences. Furthermore, the addition of ketamine was useful when the initial sedation was not satisfactory or for prolonging the immobilization period in a practical and reliable way. (tiletamine and zolazepam) and ketamine in order to obtain biological samples. During 2006/2007, 22 males were immobilized at the ...